Integrating genomic profiling to clinical data: assessing the impact of CD147 expression on plaque stability - Chen, Yu; Lu, Si; Ren, Yong; Fan, Jun; Bao, Chun-Ping; Zhang, Xin; Shi, Yan-Kun; Wang, Yan; Yang, Li-Xia (Frontiers in Cardiovascular Medicine, 2024)
Background: Acute Coronary Syndrome (ACS) continues to be a leading cause of death and illness worldwide. Differentiating stable from unstable coronary plaques is essential for enhancing patient outcomes. This research investigates the role of CD147 as a biomarker for plaque stability among coronary artery disease patients.The study began with high-throughput sequencing of blood samples from six patients, divided equally between those with Stable Angina (SA) and Unstable Angina (UA), followed by bioinformatics analysis. Expanding upon these findings, the study included 31 SA patients and 30 patients with ACS, using flow cytometry to examine CD147 expression on platelets and monocytes. Additionally, logistic regression was utilized to integrate traditional risk factors and evaluate the predictive value of CD147 expression for plaque stability.Results: Initial sequencing displayed a notable difference in CD147 expression between SA and UA groups, with a significant increase in UA patients. Further analysis confirmed that elevated platelet CD147 expression was strongly associated with unstable plaques (OR=277.81, P < .001), after adjusting for conventional risk factors, whereas monocyte CD147 levels did not show a significant difference.Elevated CD147 expression on platelets is a crucial biomarker for identifying unstable coronary artery plaques, offering insights into patient risk stratification and the development of targeted treatment strategies. This underscores the pivotal role of molecular research in understanding and managing coronary artery disease, paving the way for improved clinical outcomes.